The Bin Ladens an Arabian family in the American century - Coll, Steve (Penguin Press, 2008)
The Bin Ladens rose from poverty to privilege; they loyally served the Saudi royal family for generations--and then one of their number changed history on September 11, 2001. Journalist Steve Coll tells the story of the rise of the Bin Laden family and of the wildly diverse lifestyles of the generation to which Osama bin Laden belongs, and against whom he rebelled. Starting with the family's escape from famine at the beginning of the twentieth century, through its jet-set era in America after the 1970s oil boom, and finally to the family's attempts to recover from September 11, this book unearths extensive new material about the family and its relationship with the United States, and provides a richly revealing and emblematic narrative of our globally interconnected times.--From publisher description.